TRANSLATION TECHNIQUES OF IDIOMATIC PHRASAL VERBS IN TONYA HURLEY’S “GHOSTGIRL: LOVESICK” INTO INDONESIAN - Nindy Gladysa (Journal of English Education Program (JEEP), 2018)
This study is intended to analyze the Translation Techniques Used in translating the idiomatic phrasal verbs and the most frequent Translation Techniques used by Berliani M. Nugrahani as the translator. The Translation Techniques used in this study are adapted from Molina and Albir in 2002. This study employed a corpus-based with descriptive translation study. The Population was twenty three chapters of the novel which contain idiomatic phrasal verbs. The three chapters of the novel were selected as the sample, they were chapter 1, chapter 4, and chapter 7. In determining the sample, it is based on the consideration of the writer that the chapters contain more idiomatic phrasal verbs than the findings in other chapter, so the data gathered was more rich and varied. The data were obtained from content analysis. The Content analysis was conducted to find out 1) What are translation techniques used by Berliani M Nugrahani in translating idiomatic phrasal verbs found in “Ghostgirl: Lovesick” Novel by Tonya Hurley, and 2) What is the most frequent translation techniques used by Berliani in translating idiomatic phrasal verbs in “Ghostgirl: Lovesick” Novel by Tonya Hurley. Findings from the content analysis showed the translator used 6 out of 18 translation techniques, that are Modulation, Transposition, Establish Equivalent, Reduction, Addition, and Literal Translation. Lastly, the most frequent translation technique used is Transposition with total used 53 (43.45%) and the fewest translation technique used is Literal Translation with total used 1 (0.81%).